2018
DOI: 10.1101/gr.227116.117
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic activation of meiotic recombination near Arabidopsis thaliana centromeres via loss of H3K9me2 and non-CG DNA methylation

Abstract: Eukaryotic centromeres contain the kinetochore, which connects chromosomes to the spindle allowing segregation. During meiosis, centromeres are suppressed for inter-homolog crossover, as recombination in these regions can cause chromosome missegregation and aneuploidy. Plant centromeres are surrounded by transposon-dense pericentromeric heterochromatin that is epigenetically silenced by histone 3 lysine 9 dimethylation (H3K9me2), and DNA methylation in CG and non-CG sequence contexts. However, the role of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 123 publications
(217 reference statements)
6
185
0
Order By: Relevance
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…Unequal distribution of epigenetic marks, including cytosine methylation, is assumed to primarily contribute to the large‐scale variability in recombination rates along the chromosomes of flowering plants (Underwood et al , ). In particular, cytosine methylation around the centromeric regions of A. thaliana is about four times higher than that in the middle of the chromosome arms (Underwood et al , ). Our analysis shows that this is not the case in M. polymorpha and P. patens (Lang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of the CO breakpoints in pollen and F 2 s were highly correlated in most regions of the genome (Pearson's r 0.80~0.86, both p-value<2.2e- 16), and exhibited only 13 regions with local differences across the entire genome ( Fig. 4; Materials and Methods).…”
Section: Estimating Recombination Frequency and Landscapes From Gametesmentioning
confidence: 95%
“…Thus, the local CO rate governs the types of allelic combinations that can arise through sexual reproduction. Both environmental and genetic factors have been shown to affect CO rates and distributions; some examples are the local sequence divergence or rearrangements between the homologous chromosomes [12][13][14] , the chromatin context [15][16][17][18] , variation in DNA repair mechanisms [19][20][21][22][23][24][25][26] , and environmental stress 27,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…The average read depth per library gave 1x to 2x genome-wide coverage per individual ( Figure S2 ). Of the 1,920 Col x Ler F 2 sequenced individuals, 95% had sufficient data quality and coverage to call COs. We added data from 363 previously analyzed Col x Ler F 2 individuals (Choi et al 2016;Underwood et al 2018) that were produced using another library preparation method (Rowan et al 2015(Rowan et al , 2017 . After processing and error correction for the entire data set (see Methods), we identified 17,077 COs in 2,182 individuals (File S2).…”
Section: Generating a High-density Genome-wide Co Mapmentioning
confidence: 99%